Bez retushi . Bez retushi . Without Retouching . Без ретуши - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with economist Evgenii Saburov. Featured in the program: Saburov, Evgenii Fedorovich (Director of the Russian Government Center of Information and Social Technologies) Contributors: Torchinskii, Sergei (Anchor) Интервью с экономистом Евгением Сабуровым. В программе участвуют: Сабуров, Евгений Фёдорович (Директор Центра при Правительстве Российской Федерации информационных и социальных технологий) Создатели: Торчинский, Сергей (Ведущий/Ведущая)